Magnetotail Configuration During a Steady Convection Event as Observed by Low‐Altitude and Magnetospheric Spacecraft. Issue 10 (27th October 2018) - Sergeev, V. A.; Tsyganenko, N. A.; Angelopoulos, V.; Runov, A. V.; Singer, H. J.
Abstract: Motivated by ongoing discussion regarding the magnetic configuration in the near‐Earth and midtail regions and its role in populating the inner magnetosphere during long‐duration steady magnetospheric convection (SMC) events, we analyze a rich collection of observations during 10 hr of strong, steady solar wind driving. Auroral boundaries and regions of stretched and dipolarized magnetic field in the plasma sheet were monitored using solar electron loss cone anisotropy observed by low‐altitude spacecraft. Following a southward turning of the interplanetary magnetic field and a subsequent 3‐ to 4‐hr period of large‐scale substorm‐related reconfigurations and plasma injections, the near‐Earth magnetic configuration evolved into a nonstandard type, which lasted until the end of this SMC event (5 hr). During that time a dipolarized region with complicated Bz landscape persisted in the midtail, while the configuration was very stretched in the near tail. This was manifested as a highly depressed magnetic Bz component at geostationary orbit and as persistent nonadiabatic electron scattering at the periphery of the outer radiation belt. In addition, in situ observations suggest that a thin current sheet extended longitudinally toward the dawn terminator. In the return convection region near the terminator, observations of this azimuthal current sheet were sporadically interrupted/modulated by earthward convecting plasma structures, either remnants of reconnection‐produced plasma bubbles or flapping waves. The hybrid magnetotail configuration (dipolar in the midtail and stretched in the near tail) observed during this long‐duration SMC event poses a challenge for empirical magnetospheric modeling. Key Points: Magnetotail observations and remote sensing from low altitudes are used to monitor magnetic configuration for long steady convection event Existing models fail to predict hybrid configuration (stretched inner tail and dipolarized midtail) formed after 3 hr of intense driving Unusual azimuthal current sheet in the return convection region was sporadically modulated by earthward convecting plasma structures